Pediatric nursing made incredibly easy ! - Springhouse Interactive (firm) (Springhouse : Springhouse Interactive, 2001)
1,000 review questions for nursing students and practicing nurses who are seeking advanced certification in pediatric nursing
System requirements : Pentium 166 PC; 32 MB RAM; Windows 95 or higher; SVGA monitor capable of displaying 800 x 600 resolution (16-bit recommended); 25MB free hard disk space; 8X CD-ROM drive; mouse
System requirements: Macintosh; 64MB RAM; System 8.5 or higher; SVGA monitor capable of displaying 800 x 600 resolution (16-bit recommended); 25MB free hard disk space; 8X CD-ROM drive; mouse
Keywords: Pediatric Nursing -- examination questions